The impact of neighbourhood facilities towards the homebuyer’s buying decision for residential property in Johor Bahru - Lee, Hui Li (2019)
For each type of property has its own imposed significant that impact to the homebuyer’s buying decision. From the past research that attribute which could gave impacts to the location decision were physical, economic, social, and environment. In this study, researcher examined the impacts of the neighbourhood facilities towards the homebuyer’s buying behaviour in case study area. The research objectives of this study are to rank the impact of neighbourhood facilities as well as to determine the most critical attributes of identified neighbourhood facilities that affects the buyer’s buying decision in case study area. Besides, this study aimed to study the degree of influence of individual buyer’s demographics characteristics towards their buying behaviour for a residential property in case study area. The research adopted questionnaires survey method to approach and collect the view from respondents in case study area. In this research, the Likert scale which arrange in 5 points denoted with a number is used to examine how strongly the respondents agree with the statements. The research using methods of analysis in this study which is Relative Importance Index (RII) was used to rank the statements using 5 points Likert scale. The general finding of this study reveals that there is significant relationship between some of the identified neighbourhood facilities such as transport facilities, education institution facilities, sports and recreation facilities, medical facilities, retail facilities, and entertainment facilities towards location decision of the residential properties in Johor Bahru.